EXTH-47. THERAPEUTIC REVERSAL OF PRENATAL PONTINE ID1 SIGNALING IN DIPG. (11th November 2019) - Harris, Micah; Yadav, Vivekanand; Stallard, Stefanie; Woo, Rinette; Siddaway, Robert; Qin, Tingting; Mullan, Brendan; Miklja, Zachary; Siada, Ruby; Ravindran, Ramya; Cao, Xuhong; Pasternak, Amy; et al.
Abstract: Diffuse intrinsic pontine gliomas (DIPGs) are lethal brain tumors with no effective therapies other than radiation. Inhibitor of DNA binding (ID) proteins are key regulators of tissue and lineage-specific gene differentiation during embryogenesis. Previous work has shown that H3F3A and ACVR1 mutations increase ID1 expression in cultured astrocytes, but this has not been validated in human DIPG, nor has the regulation and targetability of ID1 been explored in DIPG. Analysis of multi-focal post-mortem tumor and normal brain tissue (n=52) as well as multiple human datasets revealed ID1 to be elevated in DIPG. Elevated ID1 was found to correlate with reduced survival in DIPG. In a multi-focal autopsy DIPG case, we found ID1 expression to be heterogeneous and to correlate with tumor invasion. Chromatin immunoprecipitation-qPCR (ChIP-qPCR) was used to quantify H3K27ac and H3K27me3 at ID1 gene regulatory regions (promoters/enhancers) in multi-focal post-mortem tissue. The ID1 loci was found to be epigenetically poised for up-regulation (elevated H3K27ac and low H3K27me3) in DIPG tissue, regardless of H3 or ACVR1 mutation status, compared to normal brain. Analysis of publically-available ISH and ChIP-sequencing data revealed elevated ID1 expression and ID1-enhancer H3K27ac in prenatal mouse hindbrain compared to prenatal forebrain, prenatal midbrain, and all postnatal brain regions. ID1 shRNA-mediated knockdown of primary human H3K27M DIPG cells (DIPG007) resulted in significantly reduced invasion and migration. As cannabidiol (CBD) has successfully been used to therapeutically target ID1 in pre-clinical models of adult human cancers, we treated DIPG007 cells with CBD and found reduced viability at clinically relevant dosing (IC50=2.4 uM) with dose-dependent reduction in ID1 protein. ID1 knockdown and CBD treatment studies in murine models of DIPG are ongoing. These findings indicate that a multifactorial (genetic and regionally-based) epigenetic upregulation of ID1 drives DIPG invasiveness and is targetable with CBD.